2019
DOI: 10.4103/ijpsym.ijpsym_307_19
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-responsive Encephalopathy as a Semblance of Neuroleptic Malignant Syndrome in a Patient with Schizophrenia

Abstract: This is an open access journal, and articles are distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as appropriate credit is given and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In keeping with the findings of our study, other authors have reported an association between central pontine myelinolysis and mood symptoms. 10 A few of the reported neuropsychiatric manifestations include agitated delirium, inappropriate affect, emotional lability, personality changes, poor judgment, emotional incontinence, and disinhibition. 11 Incidentally, some studies have shown increased connectivity between the ventral striatum and thalamus in bipolar disorders.…”
Section: Psychiatric Symptoms Have Not Been Extensively Reported In I...mentioning
confidence: 99%
“…In keeping with the findings of our study, other authors have reported an association between central pontine myelinolysis and mood symptoms. 10 A few of the reported neuropsychiatric manifestations include agitated delirium, inappropriate affect, emotional lability, personality changes, poor judgment, emotional incontinence, and disinhibition. 11 Incidentally, some studies have shown increased connectivity between the ventral striatum and thalamus in bipolar disorders.…”
Section: Psychiatric Symptoms Have Not Been Extensively Reported In I...mentioning
confidence: 99%